El lugar de la competencia digital en la enseñanza y aprendizaje de lenguas segundas y extranjeras - Rodríguez-Piñero Alcalá, Ana Isabel (2022)
The globalized Information Society that has been taking shape in the 21st century with advances in new technologies requires its members to have a series of key skills, among which digital competence stands out as part of the capacity for permanent and autonomous learning. The Covid pandemic that we have been going through for almost three years has highlighted the need to train people in digital competence in order to continue carrying out their personal, educational and professional activities in all kinds of contexts and circumstances. The consultation of catalogues, bibliometric databases and digital repositories, such as Scopus, Dialnet or Recolecta, has allowed us to verify the interests that the subject arouses in the scientific community, particularly within the area of education. Thus, there is interest in identifying those digital skills that the teacher must master, in outlining the ICT skills that students need to acquire at each educational level, or in developing activities based on the specific use of applications or digital resources (use of blogs, wikis, social networks, gamification, etc.) for second and foreign language teaching. Using a fundamentally qualitative methodology, with a descriptive-interpretative epistemological orientation based on documentary analysis, the objective of this paper is to analyse the concept of digital competence and verify the place it occupies in the process of second and foreign language acquisition, especially following the publication of the complementary volume of the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR) in 2020. To this end, a conceptual delimitation has been introduced between competence digital and a series of concepts related to it, such as digital literacy, information literacy or media competence, very present in contemporary academic, scientific, political and economic discourse; the concept of digital competence, understood as a macrocompetence, has been organized in the various (sub)competences it is made up of, and we examine the place that digital competence occupies in each person’s set of competences and in relation to the communication skills, mainly within the field of second and foreign language acquisition. After this systematic review, we conclude that, although the contributions of the complementary volume of the CEFR are undoubtedly important, they are specifically limited to audiovisual comprehension and online interaction, hence we end by proposing language activities that take into consideration all language skills and all channels of communication.